Muddying the waters? A false positive case of autoimmune psychosis. (June 2021) - Ketheesan, Sarangan; Bertram, Georgia; Adam, Robert; Stark, Anne; Scott, James G
Objective: To discuss challenges with the diagnosis of autoimmune psychosis (AP) in people with chronic psychotic disorders. Method: We present a case of a 23-year-old man with an exacerbation of treatment-refractory psychosis after receiving intravenous immunoglobulin (IVIG) for suspected AP, diagnosed 4 years after the onset of psychosis. We highlight the diagnostic and management challenges in such cases. Results: The diagnosis of AP in people with long-standing illness relies on the interpretation of non-specific clinical and laboratory findings in individuals with psychosocial problems and challenges of acceptance and adherence to complex medical investigations and treatments. Equivocal results from investigations undertaken without logical clinical reasoning can lead to inappropriate interventions that are costly and can cause iatrogenic harm. Conclusion: Psychiatrists should restrict screening for antineuronal antibodies in people with chronic psychosis to those with higher risk features such as persistent treatment refractory symptoms with concurrent neurological signs and symptoms. Further research informing the clinical circumstances for antineuronal antibody testing is needed.